Familial multiple trichoepithelioma: Case report and review of the literature. - Calle-Meneses, A.; Navarro-Escudero, M.C.; Arias-Rodríguez, C. (European Journal of Pediatric Dermatology, 2024)
Trichoepithelioma is a benign tumor originating from the matrix of the hair follicle; usually occurs solitary, sometimes multiple, sporadic or familial. In the latter case it is inherited in an autosomal dominant manner with lower expression in males and greater frequency in puberty. A case of familial multiple trichoepithelioma was reported in an adolescent with a family history of similar lesions in the mother and in one of her sisters.